Sub-Bandgap Sensitization of Perovskite Semiconductors via Colloidal Quantum Dots Incorporation - Ribeiro, Guilherme (2023)
ABSTRACT: By taking advantage of the outstanding intrinsic optoelectronic properties of perovskite-based photovoltaic materials, together with the strong near-infrared (NIR) absorption and electronic confinement in PbS quantum dots (QDs), sub-bandgap photocurrent generation is possible, opening the way for solar cell efficiencies surpassing the classical limits. The present study shows an effective methodology for the inclusion of high densities of colloidal PbS QDs in a MAPbI3 (methylammonium lead iodide) perovskite matrix as a means to enhance the spectral window of photon absorption of the perovskite host film and allow photocurrent production below its bandgap. The QDs were introduced in the perovskite matrix in different sizes and concentrations to study the formation of quantum-confined levels within the host bandgap and the potential formation of a delocalized intermediate mini-band (IB). Pronounced sub-bandgap (in NIR) absorption was optically confirmed with the introduction of QDs in the perovskite. The consequent photocurrent generation was demonstrated via photoconductivity measurements, which indicated IB establishment in the films. Despite verifying the reduced crystallinity of the MAPbI3 matrix with a higher concentration and size of the embedded QDs, the nanostructured films showed pronounced enhancement (above 10-fold) in NIR absorption and consequent photocurrent generation at photon energies below the perovskite bandgap.